Miscibility studies on polystyrene/poly(ethylene oxide) and polybutadiene-graft-polystyrene/poly(ethylene oxide) blends by dilute solution viscometry - Yilmaz, E; Yilmaz, O; Caner, H (Pergamon-Elsevier Science Ltd, 1996)
Miscibility of polyethylene oxide (PEO) with polystyrene (PS) or polybutadiene-graft-polystyrene (PBS) was investigated by dilute solution viscometry. Miscibility parameters derived from the classical Huggins equation were used to estimate the miscibility of these polymer pairs. The results, which indicated immiscibility between PS and PEO, were compared with findings in bulk reported in the literature. PBS was also found to be immiscible with PEO. The effect of temperature on miscibility was studied by the same method for a blend of PBS with 83% PEO. All miscibility parameters were observed to decrease with increasing temperature. Copyright (C) 1996 Published by Elsevier Science Ltd.
Keywords: Polymer-Polymer Miscibility; Poly(Ethylene Oxide); Compatibility; Polystyrene